A Case Report of Idiopathic Omental Infarction in an Obese Child. (16th August 2012) - Tsunoda, Tomoyuki; Sogo, Tsuyoshi; Komatsu, Haruki; Inui, Ayano; Fujisawa, Tomoo
Abstract : Omental infarction (OI) is a rare cause of acute abdomen in children. A 9-year-old girl was presented with sudden-onset intermittent right lower quadrant abdominal pain and fever (37.9°C). Physical examination revealed abdominal tenderness in the right lower quadrant with localized rebound tenderness which resembled acute appendicitis. She was obese and her BMI was on the 99th percentile. Computed tomography (CT) revealed a 5 cm ill-defined heterogeneous fatty mass with hyperattenuating streaks just beneath the abdominal wall. She was diagnosed as OI and treated conservatively with reduced meals and antibiotics. Her symptom resolved gradually and she was discharged on day 7 without complications. OI should be considered as a differential diagnosis for acute right-sided abdominal pain, especially in obese children. Enhanced CT is useful for differentiating OI from other conditions presenting with acute abdomen.